Implementasi Lean Management untuk Efisiensi Pengelolaan Linen dan Kesesuaian Standar Pencegahan dan Pengendalian Infeksi di RSU X - Sari, Rionugrah; Kodyat, Alih Germas; Sunadi, Apri (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2026)
Linen management is an important process in hospitals that is directly related to service quality and Infection Prevention and Control (IPC) efforts. This study aimed to analyze the implementation of Lean Management in linen management at the laundry unit of RSU X and to evaluate its contribution to improving process efficiency and strengthening IPC practices. The study employed an operational research design with a qualitative approach through observation, in-depth interviews, and document review. Data analysis was conducted using Value Stream Mapping, waste identification based on the eight waste concept, and root cause analysis using the 5 Whys method. The results showed that the average lead time of linen management before improvement was 534.41 minutes, with non-value-added (NVA) activities accounting for 61.11% of the total process time. The most dominant type of waste identified was Defects in Products and Information, characterized by non-compliance with work procedures, inconsistent use of personal protective equipment (PPE), and suboptimal separation of clean and dirty linen flows. As a follow-up action, Lean Kaizen interventions were implemented through the Plan-Do-Check-Act (PDCA) cycle, including the development and dissemination of standard operating procedures (SOPs), work process standardization, reinforcement of PPE compliance, and improvement of supporting facilities. After the implementation, the lead time decreased to 343.24 minutes and NVA activities were reduced to 134.47 minutes. The study concludes that Lean Management is effective in reducing waste, improving the efficiency of linen management processes, and strengthening IPC implementation in hospitals.